2020
DOI: 10.1093/jtm/taaa030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak on the Diamond Princess cruise ship: estimating the epidemic potential and effectiveness of public health countermeasures

Abstract: Background: Cruise ships carry a large number of people in confined spaces with relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
433
5
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(486 citation statements)
references
References 17 publications
29
433
5
19
Order By: Relevance
“…The high attack rates on the cruise ship Diamond Princess in Japan, with more than 700 on board infected out of approximately 3700 cruise ship passengers and crew members by Feb 28, 2020, despite public health measures, suggest a very high transmissibility. 40 A fourth explanation is that the clinical spectrum is different. China's initial case definition was focused on pneumonia, and initial case fatality rates (CFR) were reported at about 10% on the basis of this narrow case definition.…”
Section: Prevention Of Global Spreadmentioning
confidence: 99%
“…The high attack rates on the cruise ship Diamond Princess in Japan, with more than 700 on board infected out of approximately 3700 cruise ship passengers and crew members by Feb 28, 2020, despite public health measures, suggest a very high transmissibility. 40 A fourth explanation is that the clinical spectrum is different. China's initial case definition was focused on pneumonia, and initial case fatality rates (CFR) were reported at about 10% on the basis of this narrow case definition.…”
Section: Prevention Of Global Spreadmentioning
confidence: 99%
“…However, the implementation of isolation and quarantine procedures helped prevent the spread of COVID-19 in more than 2,000 passengers and lowered the R 0 to 1.78. 6 Although the experience of this cruise ship provided a good model for understanding the behavior of COVID-19 spread, the spread of disease could have been prevented if all passengers and crew were evacuated early.…”
Section: International Conveyance (Diamond Princess)mentioning
confidence: 99%
“…At the time of writing, a significant number of cases had occurred in the Far East. It is incontestably contagious, as a quasiexperimental study on the Diamond Princess cruise ship showed that confinement of infected patients with uninfected patients resulted in rapid infection of the uninfected patients, leading to 700 additional cases on board [21]. However, coronaviruses in common circulation remain predominant because of their global distribution and their non-negligible mortality [14,22].…”
Section: Introductionmentioning
confidence: 99%